Alcohol use, physical activity, and muscle strength moderate the relationship between body composition and frailty risk among people living with HIV. (20th October 2022) - Levitt, Danielle E.; Simon, Liz; Lin, Hui‐Yi; Siggins, Robert W.; Ferguson, Tekeda F.; Molina, Patricia E.; Welsh, David A.
Abstract: Background: Antiretroviral therapy has improved life expectancy among people living with HIV (PLWH). Despite increased longevity, PLWH are at increased risk of age‐related comorbidities, including frailty. We examined the relationship between body composition and frailty among PLWH, and moderation of this relationship by substance use, physical activity (PA), and physical function. Methods: Participants ( n = 341; 71% male, 48 ± 10 years, body mass index (BMI) = 27.3 ± 7.0 kg/m 2 ) enrolled in the New Orleans Alcohol Use in HIV (NOAH) study underwent measures of body composition, muscle strength, and gait speed. Whole blood phosphatidylethanol (PEth) was measured, and substance use and PA were self‐reported. Frailty risk measures included the 58‐Item Deficit Index (DI58) and the Veterans Aging Cohort Study (VACS) Index 1.0, where higher scores indicate greater frailty risk. Results: Multivariable linear regression adjusted for age, sex, and race showed that higher fat‐free mass index (FFMI), body fat (%), waist‐to‐hip ratio, and body mass index (BMI) ≥ 25.0 kg/m 2 vs. < 25.0 kg/m 2 were significantly ( p < 0.05) associated with decreased frailty risk measured by the VACS Index, whereas adjusted analyses showed no association between body composition variables and the DI58 score. Recent alcohol use, muscle strength, and PA, but not lifetime alcohol use or gait speed, significantly moderated associations between body composition variables and frailty risk with medium‐to‐large effect sizes. Subgroup analyses revealed a negative relationship between DI58 and FFMI among people with PEth > 8 ng/ml and negative relationships of VACS Index with FFMI and WHR in people with lower muscle strength. Overweight or obese BMI categories were positively associated with DI58 in people with lower muscle strength or higher PA level but negatively associated in those with higher muscle strength. Conclusions: Our findings indicate that body composition has significant modulatory effects on frailty risk in PLWH, where obesity increases the risk of frailty and greater muscle mass may be protective, even in individuals who use alcohol. These results highlight the importance of considering body composition, physical activity, and physical function in assessing frailty risk in PLWH, particularly among individuals who use alcohol. Moreover, they support the implementation of physical activity interventions to ameliorate the risk of frailty in aging PLWH. Abstract : Results from this study reveal that fat‐free mass, abdominal adiposity, body fat percentage, and body mass index are associated with frailty risk among people living with HIV (PLWH). Key moderators of these relationships include recent alcohol use, muscle strength, and physical activity level. Findings suggest that clinicians should focus on improving fat‐free mass quantity among their patients living with HIV, particularly among those with lower grip strength and those who use alcohol.